Special steels and composite materials for lighter, more eco-friendly merchant ships. (Research'eu results magazine)
Today's passenger and cargo ships are increasingly large and complex. An EU initiative replaced conventional steel with other materials to minimise their susceptibility to cracking in areas where stress concentrates due to fatigue loads.